Proposed interior design of Roller Sports Center at Lot 2395,Seksyen 41, Jalan Sultan Ismail, 50350 Kuala Lumpur for Kelab Inline Skate Titiwangsa / Azzureen Sulaiman - Sulaiman, Azzureen (Faculty of Architecture, Planning and Surveying, 2012)
Inline skating is a form of recreation as well as a sport. This sport are getting known by Malaysian lately. In order to introduce this sports to Malaysian, Kelab Inline Skate Titiwangsa with their good intention, wanted to open a centre where all the inline skating lover can gather and share their skills together with the experts. In addition, Kelab Inline Skate Titiwangsa trained their club members and sent them to take part in skating competition in Malaysia and also to SEA Games. This project is introducing new scheme design of a Roller Sports Centre at Lot 2395, Seksyen 41, Jalan Sultan Ismail, 50350 Kuala Lumpur for Kelab Inline Skate Titiwangsa. The main target people is Malaysian aged 4 to 40 years old especially youngsters whoever interested with inline skates sports. Due to the wide range of skates and customers come from different ages, backgrounds and races, the concept must be suitable for each individual and must be comfortable for the skaters. The concept also must be able to give a positive effect and confident to the skaters to play and practising their skills. However, to achieve a good final design, a few research have to be done to identify the client background and the club member’s aims, the type of activities in the centre, the space planning, type of services and facilities, that will be provided, the business operation time and other related information. The aim of this project is to fulfill the designer’s and client’s needs in their planning to design new Roller Sports Center to create and provide accommodation space in a building. The objective of this project is to provide accommodation space in a building, to provide a gathering place for club members, to introduce inline skate sports to Malaysians and to create a new lifestyle of design as a sport centre. As the proposed site is a single building with compound, so the scope of activities could be indoor and outdoor which is suitable for inline skating sport. The proposed site located near the monorail station which can be accessed easily by youngsters since the target market is young generation.